The Implementation of the Discovery Learning Model with Digital Media in Writing Narrative Texts in Elementary Schools - Partini; Farida Nugrahani; Mukti Widayanti (Elementary Teacher Education Program, Majalengka University, 2025)
This study aims to describe the planning, implementation, challenges, and solutions in teaching narrative writing using the Discovery Learning model based on digital media to fifth-grade students at SDN 01 Wonosari, Gondangrejo, Karanganyar for the 2024/2025 academic year. The research method used is descriptive qualitative. The data used in this study includes information about planning, implementation, challenges, and solutions in teaching narrative writing. The data sources include teachers, students, and related documents such as the Lesson Plan, learning activities and evaluation results. Data were collected through observation, semi-structured interviews, and document analysis. The sampling technique used is purposive sampling. The validation technique uses source and technique triangulation to ensure the validity of the data. Data analysis was carried out using the Miles and Huberman interactive model through three stages: data reduction, data presentation, and conclusion drawing/verification. The results of the study show that: 1) the lesson planning involves selecting interesting themes, using digital media, and systematic evaluation and feedback; 2) the implementation went well, with students actively engaging in exploring the material using digital media, and the teacher facilitating the learning process in accordance with the Discovery Learning model; 3) challenges arose in the use of technology by students and time management by the teacher; 4) proposed solutions include technical training for students and teachers, as well as flexibility in schedule management to optimize the learning process. This study provides insights into the effectiveness of the Discovery Learning model based on digital media in improving students' narrative writing skills, as well as the importance of technology readiness and structured evaluation in learning.